Effects of digital economy-driven Chinese-style agricultural modernisation--based on analysis of mediating effects and spatial spillovers - Hong, Pan; Shuang, Tan; Mingyu, Liu; Xie, Ying; Long, Suwan (Cheng) (Elsevier, 2026)
Agricultural modernisation is central to rural development and long-term food security, yet its pathways remain uneven across space. In the context of China's rapid digital expansion, this study examines how the digital economy reshapes agricultural modernisation and rural transformation. Using panel data for 30 Chinese provinces from 2014 to 2023, we construct comprehensive indices of the digital economy and agricultural modernisation and apply fixed-effects and spatial econometric models to analyse direct effects, mediating mechanisms, and spatial spillovers. The results show that the digital economy significantly advances agricultural modernisation by enhancing productivity, resilience, and product quality. Technological innovation acts as an important mediating channel, amplifying the modernising effects of digitalisation. We also identify strong spatial spillover effects, indicating that digital economy development in one region can promote agricultural modernisation in neighboring regions. These effects are spatially heterogeneous, with stronger impacts observed in western provinces and major grain-producing and production–marketing balance areas. By revealing the mechanisms and spatial dynamics through which the digital economy influences agriculture, this study contributes to debates on digitalisation, rural inequality, and uneven rural transformation, and offers policy-relevant insights for digitally enabled rural development in China and other emerging economies.
Keywords: 44 Human Society; 2 Zero Hunger; Geography; 4404 Development studies; 4406 Human geography; 4410 Sociology; Digital economy; Agricultural modernisation; Technological innovation; Intermediary effects; Spatial spillover effects